The Urgency of Financial Management of Micro, Small and Medium Enterprises (MSMEs) Grocery Stores with Accounting Management - wahyono, Tries edy; Pakage , Ferdinant; Widjanarko , Bambang; Fahmi, Moh Farih; Abd Raihan; Puspitasari, Ira (Universitas Kristen Cipta Wacana, 2024)
This study aims to determine the state of financial redulation of grocery stores in Malang and the opinions of business people regarding the application of accounting-based financial science. This research was conducted using a descriptive method with a qualitative approach, which is based on the results of observations and interviews with informants. Three business owners of grocery stores in Malang became informants in this study, namely informant A, informant B, and informant C. The three informants did not have basic knowledge related to the financial management of grocery stores in Malang. The three informants do not have basic knowledge related to financial management, nor have they participated in financial training from government agencies or private agencies. Based on the results of the brief research above, it can be concluded that the MSME players of Grocery Stores in Malang who have been selected by the researcher, do not fully know the importance of applying accounting science in managing their business finances. In addition, there must be support from the government to facilitate this accounting-based financial management knowledge, taking into account the opinions of business actors, if they cannot leave the business to attend training, it can be facilitated online.